’Manifestations and Extent of Climate Change’. The Case of Merti District, Arsi Zone, Oromiya Region, Ethiopia - Eshete, Mulugeta; Tesfaye, Yemiru; Teklegiorgise, Yoseph (International Journal of Climate Research, 2017)
Climate change threat has got a pronounced impact throughout the world. This study assessed the manifestations and extent of climate change in Merti district, Arsi zone, Oromia Regional state, Ethiopia. The study examined the indicators and perceptions of climate change by local farmers, and climate trend of the area. The study was based on key informant interviews, focus group discussions, household survey questionnaire and time series meteorological temperature and rainfall climate data. Respondents confirmed the variability in rainfall frequent delay, showing irregular patter both at the start and end of the rainy season which usually begin latter or end up earlier , unreliable distribution, erratic a general decreasing trend of rainfall was observed and an increasing warming trend with respect to temperature and abnormal conditions like occurrence of unseasonal, unusual and extreme high and low rain, occurrence of extreme hot and cold temperature, and frequent happening of drought and flood, forest and vegetation cover destruction and diminishing formerly existing wild animals, crop cultivation and livestock production decline are indicators of climate change and variability and burning issues for all the communities in the study area. The recorded time series meteorological temperature and rainfall climate data (1990–2014) also showed an increasing trend in temperature and high inter-annual and intra-seasonal rainfall variability.